The E-wave propagation index (EPI): A novel echocardiographic parameter for prediction of left ventricular thrombus. Derivation from computational fluid dynamic modeling and validation on human subjects - Harfi, Thura T.; Seo, Jung-hee; Yasir, Hayder S.; Welsh, Nathaniel; Mayer, Susan A.; Abraham, Theodore P.; George, Richard T.; Mittal, Rajat (International journal of cardiology, 2017)
To describe the derivation and validation of a novel echocardiographic metric for prediction of left ventricle thrombus (LVT). Computational fluid dynamic modeling using cardiac CT images was used to derive a novel echocardiography-based metric to predict the presence of LVT. We retrospectively reviewed 25 transthoracic echocardiograms showing definite LVT (LVT group). We then randomly selected 25 patients with LVEF ≥55% (Normal EF group) and 25 patients with severe cardiomyopathy (CMP) with LVEF ≤40% without evidence of LVT (CMP group). The E-wave Propagation Index (EPI) was measured as the E-wave velocity time-integral divided by the LV length. An EPI>1 indicates penetration of the mitral jet into the apex whereas an EPI<1 is indicative of incomplete apical washout. The mean EPI was compared between the three groups. Crude and adjusted odd ratios of EPI and LVT association were also measured. Mean EPI was highest for the normal EF group and lowest in the LVT group (1.7 vs. 0.8; p<0.0001). Mean EPI also differed significantly between LVT and CMP groups (0.8 vs. 1.2; p<0.0001). 88% of the LVT group had EPI <1.0 compared to only 20% of the CMP group (p<0.0001). Among the LVT and CMP groups, an EPI <1 increased the odd ratio of LVT by 53.7 times (95% CI: 6.9–416) controlling for LVEF and LV volume. The E-wave propagation index is a novel, easily-obtainable, echocardiographic metric to evaluate apical LV flow. An EPI of less than 1 is an independent predictor of LVT formation.